THE ROLE OF KNOWLEDGE MANAGEMENT AS DEVELOPING LIBRARIAN COMPETENCIES - Syahrianda, Muhamad Salwan (PERSPEKTIF: Journal of Social and Library Science, 2023)
(Objectives) This study aims to determine the role of knowledge management in improving the competence of a librarian. (Method) This study uses the research method used, namely literature study with the scope of the keywords Knowledge Management; Librarian Competence; Libraries; Librarian. (Findings) Knowledge Management has an influence in developing the competence of a librarian. With knowledge management will create a good work culture for an organization. In knowledge management there is a process, namely knowledge sharing where it can exchange information from members of the organization so that librarians can improve their abilities both through discussion, work experience, and existing information sources in meeting their information needs.